The effects of a seeding process on the cryopreservation of cellular suspensions of prepubertal testis - (:unkn) unknown (MARMARA UNIV, FAC MEDICINE, 2015)
Objective: The cryopreservation of prepubertal testicular tissue promises to preserve fertility in boys under cancer treatment. The effects of a seeding process was investigated using different carriers for prepubertal testicular cell suspensions in order to develop an appropriate method for cryopreservation. Materials and Methods: Testicular cell suspensions of 7-8 day old male Wistar rats were frozen by a programmed slow freezing method. The straw and cryotube selected as carriers underwent a seeding process. The morphological effects on spermatogonial stem cells and Sertoli cells were evaluated semi-quantitatively by light microscopy and qualitatively with a transmission electron microscope. Results: The rate of vitality with or without seeding in straw was respectively, 90.6% (+/- 3.0), 89.4 (+/- 1.3) and in cryotube 77.6 (+/- 4.2) and 85.4 (+/- 2.7). The seeding process, showed no significant difference between the straw groups, but a significant difference was seen between the cryotube groups (p< 0.0001). The nuclei, cytoplasmic structures and membranes of Sertoli and spermatogonial stem cells, showed less degeneration in the straw than in the cryotubes when the seeding process was applied. Conclusion: In this study, we compared two carriers to observe the effect of seeding during cryopreservation of prepubertal testicular cell suspensions and found that seeding in straw was the preferable. Keywords:
Keywords: Prepubertal testis; Testicular cell suspension; Programmed slow freezing; Spermatogonial stem cell; Seeding process; HUMAN TESTICULAR TISSUE; SPERMATOGONIAL SURVIVAL; FERTILITY PRESERVATION; STEM-CELLS; TRANSPLANTATION; EXPERIENCE; PROTOCOLS; GLYCEROL